Oral Neutrophil Free Fatty Acid Receptors Expression May Link Oral Host and Microbiome Lipid Metabolism - Wzatek, Martin; Bahammam, Shaima; Buiga, Petronela; Haddad, Kendal; Sima, Corneliu (Frontiers in Oral Health, 2022)
In health, commensal bacteria from oral biofilms stimulate polymorphonuclear neutrophil (PMN) recruitment in gingival sulci and the oral cavity. Oral PMN (oPMN) is short-lived cells with low prosurvival gene expression. In periodontitis, oPMN accumulates in higher numbers, has extended lifespan, and sustains nonresolving inflammation. We hypothesize that short- and long-chain free fatty acids (SCFAs and LCFAs) and lipid mediator resolvin E1 (RvE1) modulate host ability to control biofilms and resolve inflammation. Our objective was to measure oPMN surface expression of receptors FFAR2 (binds bacteria-derived SCFA), FFAR4 (binds LCFA, EPA, and DHA), and ERV1 (binds RvE1) in health and to assess sex differences. We included 20 periodontally healthy individuals aged 20–80 years (10 males, 10 females), who were asked to (1) answer a targeted health nutritional questionnaire and (2) provide an oral saline rinse. oPMN isolated by sequential filtration was labeled with fluorophore-conjugated antibodies against CD11b, CD14, CD16, CD66b, ERV1, FFAR2, and FFAR4 and analyzed by flow cytometry. Statistical analyses were the following: two-way ANOVA, Tukey's test, and Pearson's correlation. Oral rinses contained 80% oPMN of which 60% were ERV1+ and FFAR2+, and 10% FFAR4+, with no sex differences. Females had more oPMN ERV1 compared to males. Both sexes had higher ERV1 compared to FFAR2 and FFAR4. CD66b+CD16high oPMN expressed less ERV1 and FFAR2 compared to CD66b+CD16low. There were positive correlations between oPMN ERV1 and FFAR2 expression and between ERV1+ and FFAR2+ oPMN and fish intake. These findings will help to better understand how oral host and microbiome interactions maintain periodontal health.